Dreaming in Code: Two Dozen Programmers, Three Years, 4,732 Bugs, and One Quest for Transcendent Software - Scott Rosenberg (Crown Publishers, 2007)
Why is software so hard? Hard to make well. Hard to deliver on time. Hard to use. Our civilization runs on software, yet the art of creating it continues to be a dark mystery, even to the experts, and the greater our ambitions, the more spectacularly we seem to fail. This book sets out to understand why, through the story of one software project--Mitch Kapor's Chandler, an ambitious, open-source effort to rethink the world of email and scheduling. Journalist Rosenberg spent three years following the work of the Chandler developers as they scaled programming peaks and slogged through software swamps. Here he tells their stories.--Adapted from www.dreamingincode.com.